Natural and engineered biosynthesis of nucleoside antibiotics in Actinomycetes. (1st March 2016) - Chen, Wenqing; Qi, Jianzhao; Wu, Pan; Wan, Dan; Liu, Jin; Feng, Xuan; Deng, Zixin
Abstract: Nucleoside antibiotics constitute an important family of microbial natural products bearing diverse bioactivities and unusual structural features. Their biosynthetic logics are unique with involvement of complex multi-enzymatic reactions leading to the intricate molecules from simple building blocks. Understanding how nature builds this family of antibiotics in post-genomic era sets the stage for rational enhancement of their production, and also paves the way for targeted persuasion of the cell factories to make artificial designer nucleoside drugs and leads via synthetic biology approaches. In this review, we discuss the recent progress and perspectives on the natural and engineered biosynthesis of nucleoside antibiotics.